A Look Back at Where English and U.S. Arbitration Law Comes From: The Long 18th Century. Issue 8 (28th August 2021) - Samuel, Adam
Abstract : Two great English enthusiasts for arbitration history, Derek Roebuck and Johnny Veeder, died in the spring of 2020. Derek was a legal historian and an author of a series of books on the subject. Johnny was one of the top English practicing barristers and arbitrators.